EDUKASI PENCEGAHAN DEHIDRASI PADA ANAK SAKIT SELAMA DI RUMAH - Wulandari, Puput; Pangestuningtyas, Trisna (Politeknik Kesehatan Kemenkes malang, 2024)
Dehydration is one of the most common emergencies in children, especially infants (under 1 year old). This is because the percentage of fluid in infants is greater than adults. In infants aged < 1 year, body fluids are around 80-85% of body weight and in children aged > 1 year, they contain 70-75% water. While in adults, the amount of body fluids is approximately 50-60% of body weight. According to the World Health Organization, (2019) there are approximately 1.7 billion cases of diarrhea with a mortality rate of 525,000 children under five every year. In developing countries, children under 3 years of age experience an average of 3 episodes of diarrhea per year. Based on survey data from the Indonesian Health Profile Report in 2020, the reported incidence of diarrhea in children under five was 3,953,716 cases. The second highest diarrhea mortality rate after pneumonia in the toddler group (12-59 months) was 201 cases. The research method was carried out by providing counseling After the educational counseling was carried out on the prevention of dehydration of sick children while at home to parents (mothers), the officer asked back to the target regarding the material that had been delivered. The target understands the material that has been delivered by the officer. With this activity, it is hoped that parents will prevent dehydration at home